The semantic and lexical level of bilingualism in protest ages - Al-Rhawi, Mohammad Khaled (Journal of Arabic Language Sciences and Literature, 2024)
The first-century bilingual research addresses Hijri at the semantic and lexical level, starting with a pave between the five levels of linguistic performance: Quranic performance level, poetic performance level, official performance level, paltry performance level, and daily performance level. He then referred to bilingual levels: The lexicon level, the acoustic level, the pure level, the grammar level, and the research was conducted at the lexical level that appeared in two manifestations. The first appearance was the difference in the connotations of a single term between tribes. This was highlighted in three issues: the multiplicity of names and the multiplicity of connotations of a single word. The second manifestation was the multiplicity of words indicative of the same meaning, highlighted in two issues, namely, the proliferation of names for one name and synonyms, which provided many linguistic testimonies explaining what was meant in each aspect of this level of bilingualism, and then concluded with the most notable results.